Subcultural, ideological, and valence-based differences in caregiver reminiscing functions. Issue 2 (7th February 2021) - Klemfuss, J. Z.; Slonecker, Emily M.; Akhavein, Kimia; Dhruve, Deepali M.
ABSTRACT: Researchers have identified cultural differences in caregiver beliefs about the functions of parent–child reminiscing. However, this work has largely been limited to comparisons between Asian or Asian American and European American caregivers discussing autobiographical events, broadly. In the present study, 365 caregivers of 3- to 12-year-old children from four U.S. subcultures (African, Asian, European, and Hispanic/LatinX) reported about the functions of discussing positive and negative past events with their child, and about their collectivist values. Overall, positive events were discussed more often than negative events and all reminiscing functions were endorsed more strongly for positive events. European Americans endorsed directive functions for positive events least of the three primary functions, and endorsed them less than the other three subcultural groups. All four subculture groups endorsed directive functions equally and more strongly than other functions when discussing negative events. More collectivist attitudes predicted stronger endorsement of all conversation functions except directive functions for negative events. This research is poised to expand our understanding of how caregivers from different subcultural groups, and with different culture-based values, may attempt to shape their children's worldview through reminiscing and how the functions caregivers emphasise shift depending on the valence of the event under discussion.